Guest Editorial: Copyright Problems in Library Services - Madhava Menon, N.R. (DESIDOC Journal of Library & Information Technology, 2003)
Information is the key to development both for individuals and nation. Technology has now opened up infinite possibilities for accessing a whole range and wide variety of information in as cale unprecedented then ever before the information highway and the digital technology have pushed info insignificance the conventional library systems and revolutionised the scope for accessing information with speed, accuracy and comprehensiveness. http://dx.doi.org/10.14429/dbit.16.6.3285